Localized Blistering Eruption of the Face and Neck – A Case Study and Differential Considerations - Michalska-Jakubus M; Wdowiak-Filip A; Kowalewski C; Woźniak K; Krasowska D (Dove Medical Press, 2022)
Małgorzata Michalska-Jakubus,1 Anita Wdowiak-Filip,2 Cezary Kowalewski,3 Katarzyna Woźniak,3 Dorota Krasowska1 1Department of Dermatology, Venereology and Pediatric Dermatology, Medical University of Lublin, Lublin, Poland; 2Department of Cosmetology and Aesthetic Medicine, Medical University of Lublin, Lublin, Poland; 3Department of Dermatology, Immunodermatology and Venereology, Medical University of Warsaw, Warsaw, PolandCorrespondence: Anita Wdowiak-Filip, Staszica 11, Lublin, 20-081, Poland, Tel +48 798 64 75 07, Email anita.wdowiak@gmail.comAbstract: We describe a 36-year-old woman with erythematous lesions and well-tense blisters confined to the face and neck of two months history, without mucosal involvement and no triggering factors. A lesional skin biopsy showed a subepidermal blister. Direct immunofluorescence of peribullous skin identified linear deposits of IgG, IgA, and C3 complement along the basement membrane zone, whereas indirect immunofluorescence was negative. Using fluorescence overlay antigen mapping by laser scanning confocal microscopy, linear immunoglobulins deposits were found to be located above collagen IV and below laminin 332 (formerly named laminin 5), in a pattern typical of mucous membrane pemphigoid (formerly named cicatricial pemphigoid). Consequently, in terms of the clinical picture and confocal study, a rare variant of mucous membrane pemphigoid was established, namely Brunsting-Perry type. Combined therapy with oral prednisone and dapsone healed the lesions, leaving atrophic scars and milia. The paper also provides a review of previous reports on this item as well as a comprehensive differential diagnosis of facial blistering lesions.Keywords: mucous membrane pemphigoid, Brunsting-Perry pemphigoid, laser scanning confocal microscopy